Simulation, simplicity, and selection: an evolutionary perspective on high-level mindreading. - Schulz, Armin W. (Philosophical Studies, 2011)
In this paper, I argue that a natural selection-based perspective gives reasons for thinking that the core of the ability to mindread cognitively complex mental states is subserved by a simulationist process-that is, that it relies on non-specialised mechanisms in the attributer's cognitive architecture whose primary function is the generation of her own decisions and inferences. In more detail, I try to establish three conclusions. First, I try to make clearer what the dispute between simulationist and non-simulationist theories of mindreading fundamentally is about. Second, I try to make more precise an argument that is sometimes hinted at in support of the former: this 'argument from simplicity' suggests that, since natural selection disfavours building extra cognitive systems where this can be avoided, simulationist theories of mindreading are more in line with natural selection than their competitors. As stated, though, this argument overlooks the fact that building extra cognitive systems can also yield benefits: in particular, it can allow for the parallel processing of multiple problems and it makes for the existence of backups for important elements of the organism's mind. I therefore try to make this argument more precise by investigating whether these benefits also apply to the present case-and conclude negatively. My third aim in this paper is to use this discussion of mindreading as a means for exploring the promises and difficulties of evolutionary arguments in philosophy and psychology more generally.